Monoclonal Antibodies as Treatment Modalities in Head and Neck Cancers - Vivek Radhakrishnan (AIMS Medical Science, 2015)
The standard treatments of surgery, radiation, and chemotherapy in head and neck squamous cell carcinomas (HNSCC) causes disturbance to normal surrounding tissues, systemic toxicities and functional problems with eating, speaking, and breathing. With early detection, many of these cancers can be effectively treated, but treatment should also focus on retaining the function of the proximal nerves, tissues and vasculature surrounding the tumor. With current research focused on understanding pathogenesis of these cancers in a molecular level, targeted therapy using monoclonal antibodies (MoAbs), can be modified and directed towards tumor genes, proteins and signal pathways with the potential to reduce unfavorable side effects of current treatments. This review will highlight the current MoAb therapies used in HNSCC, and discuss ongoing research efforts to develop novel treatment agents with potential to improve efficacy, increase overall survival (OS) rates and reduce toxicities.